Alpha-1 antitrypsin inhibits formaldehyde-induced apoptosis of human peritoneal mesothelial cells. Issue 2 (March 2020) - Lim, Jeong-Hoon; Park, Sang Mi; Yook, Ju-Min; Ahn, Ji-Sun; Choi, Soon-Youn; Oh, Se-Hyun; Jung, Hee-Yeon; Choi, Ji-Young; Cho, Jang-Hee; Park, Sun-Hee; Kim, Yong-Lim; Kim, Chan-Duck
Background: The alpha-1 antitrypsin (AAT) protein has an important role in the anti-inflammatory and apoptotic response. AAT inhibits not only serine proteases but also cysteine and aspartic proteases. Apoptosis results from the sequential activation of cysteine proteases of the caspase family. This study aimed to evaluate the effect of AAT on formaldehyde-induced apoptosis of human peritoneal mesothelial cells (HPMCs). Methods: HPMCs were cultured and treated with formaldehyde (250 µM) to induce apoptosis. In the AAT group, the cultured HPMCs were pretreated with AAT (2 mg/mL) for 1 h before formaldehyde treatment. We used 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays to determine cell viability, and flow cytometry and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) assays to detect apoptosis. The MTT assays were used to find optimal concentrations of formaldehyde and AAT. We measured caspase-3 activity and used Western blotting to estimate Bcl-2 and Bad expression. Results: Flow cytometry and TUNEL assays revealed that formaldehyde exposure significantly increased apoptosis compared with the control treatment, but pretreatment with AAT significantly inhibited this effect. Compared with the control, caspase-3 activity was significantly increased and the ratio of Bcl-2 to Bad expression significantly decreased following treatment with formaldehyde. However, caspase-3 activity was significantly lower and the Bcl-2 to Bad expression ratio higher in the AAT group than in the formaldehyde-only group. Conclusion: AAT inhibits formaldehyde-induced apoptosis of HPMCs via a caspase-mediated pathway. These data support a potential use for AAT as a therapeutic agent for the inhibition of peritoneal cell apoptosis during peritoneal dialysis.